GLOBAL PERSPECTIVES ON MOTIVATION IN EFL LEARNING: A SYSTEMATIC LITERATURE REVIEW - Sitorus, Budianto; Sulistyowati, Tussi; Hermansyah, Sam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
This systematic literature review delves into the varied global motivations shaping English as a Foreign Language (EFL) learning within diverse university contexts. Examining Tay Do University in Vietnam, the study illuminates a blend of intrinsic and extrinsic factors contributing to moderate motivation levels. Lithuania's emphasis on instrumental orientation among university students showcases the multifaceted nature of motivation. In Sweden, the research brings attention to challenges faced by newly arrived students, suggesting a need for policy adjustments to address these issues effectively. Indonesian graduates opt for informal education to enhance English proficiency, underlining the importance of diverse methods and success stories in the learning process. Cambodia's exploration reveals nuanced motivational orientations among university students. French higher education students exhibit diverse attitudes toward EFL learning, Japan displays a positive outlook, Saudi students lean towards extrinsic motivations, and Taiwan emphasizes the creation of motivated learning experiences. These findings collectively offer valuable insights for refining teaching strategies, making informed policy adjustments, and inspiring further research initiatives within the realm of EFL learning. Ultimately, this comprehensive review contributes to a deeper understanding of the multifaceted nature of motivations influencing EFL learners globally.